ANALYSIS OF INTEREST IN INVESTING WITH FINANCIAL LITERACY AS MODERATOR: THEORY OF PLANNED BEHAVIOR APPROACH - Lingga, Ita Salsalina; Marpaung, Elyzabet Indrawati; Thedya, Ranesya (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
The capital market is currently an attractive option for investors, including millennials. The rapid advancement of technology had an impact on increasing the interest of the millennial generation to invest because it is easier to do. Success in investing is one of them determined by financial literacy. The latest data explains the change in the type of securities investors dominated by millennials and Gen Z. This news is clear evidence of a shift in mindset from millennials. The question of how is the behavior of millennials relating to investment and are they equipped with adequate financial literacy has encouraged the development of research using the theory of planned behavior in order to prove that interest in investing is determined by behavioral factors and strengthened by financial literacy as moderator. The selection of the research sample was focused on students of Accounting Program at Maranatha. The data analysis was carried out using SEM PLS as a method of choice. The processed data produce evidence that interest in investing is positively determined by behavioral factors including attitudes, subjective norms and perceived behavioral control. On the other hand, the interaction of behavioral factors on investment interest has not been proven to be strengthened by financial literacy.